Acceso a los servicios de salud en seis ciudades de Colombia : limitaciones y consecuencias (2009)
ABSTRACT: To understand the characteristics of access to the General System of Social Security in health (SGSS), from the perspective of doctors, nurses, administrators and users. Methodology: based on the grounded theory we present a study in six cities in Colombia: Barranquilla, Bucaramanga, Bogota, Leticia, Medellín and Pasto, for which interviews were conducted in-depth with health professionals involved in service delivery and focus groups with service users. Results: The findings indicate that insurance has become an end in itself, and being affiliated to SGSSS does not guarantee effective access to services. The dominance of the market, the financial profitability of insurers, imposed cost-containment mechanisms over the right to health. There are limitations from the rules, benefit plans that create geographical, economic and cultural barriers from the various actors involved in the chain of decisions. Additionally, display individual and institutional ethical shortcomings, clientelism and corruption in the management of resources, coupled with poverty and geographical dispersion of communities, mean that further limiting access to health services.